Effectiveness of integrated nursing interventions for fatigue in patients with advanced cancer: a systematic review of randomized controlled trials - Zuo Xiao-Lin; Wen Yan; Gong Shang-Qun; Meng Fan-Jie (Sciendo, 2019)
To evaluate the effectiveness of integrated nursing interventions for fatigue in patients with advanced cancer.